Associations between the psychological health of patients and carers in advanced COPD - Mi E; Mi E; Ewing G; Mahadeva R; Gardener AC; Holt Butcher H; Booth S; Farquhar M (International Journal of COPD, 2017)
Ella Mi,1 Emma Mi,1 Gail Ewing,2 Ravi Mahadeva,3 A Carole Gardener,4 Hanne Holt Butcher,4 Sara Booth,5 Morag Farquhar6 On behalf of the Living with Breathlessness Study Team 1School of Clinical Medicine, 2Centre for Family Research, University of Cambridge, 3Department of Respiratory Medicine, Cambridge University Hospitals NHS Foundation Trust, 4Department of Public Health and Primary Care, Institute of Public Health, 5Department of Oncology, University of Cambridge, Cambridge, 6School of Health Sciences, University of East Anglia, Norwich, UK Objective: Anxiety and depression are highly prevalent in patients with COPD and their informal carers, and associated with numerous risk factors. However, few studies have investigated these in primary care or the link between patient and carer anxiety and depression. We aimed to determine this association and factors associated with anxiety and depression in patients, carers, and both (dyads), in a population-based sample.Materials and methods: This was a prospective, cross-sectional study of 119 advanced COPD patients and their carers. Patient and carer scores ≥8 on the Hospital Anxiety and Depression Scale defined symptoms of anxiety and depression, χ2 tests determined associations between patient and carer symptoms of anxiety/depression, and χ2 and independent t-tests for normally distributed variables (otherwise Mann–Whitney U tests) were used to identify other variables significantly associated with these symptoms in the patient or carer. Patient–carer dyads were categorized into four groups relating to the presence of anxious/depressive symptoms in: both patient and carer, patient only, carer only, and neither. Factors associated with dyad symptoms of anxiety/depression were determined with χ2 tests and one-way analysis of variance for normally distributed variables (otherwise Kruskal–Wallis tests).Results: Prevalence of symptoms of anxiety and depression was 46.4% (n=52) and 42.9% (n=48) in patients, and 46% (n=52) and 23% (n=26) in carers, respectively. Patient and carer symptoms of anxiety/depression were significantly associated. Anxious and depressive symptoms in the patient were also significantly associated with more physical comorbidities, more exacerbations, greater dyspnea, greater fatigue, poor mastery, and depressive symptoms with younger age. Symptoms of carer anxiety were significantly associated with being female and separated/divorced/widowed, and depressive symptoms with younger age, higher educational level, and more physical comorbidities, and symptoms of carer anxiety and depression with more unmet support needs, greater subjective caring burden, and poor patient mastery. Dyad symptoms of anxiety/depression were significantly associated with greater patient fatigue.Conclusion: Symptoms of anxiety and depression in COPD patients and carers are significantly associated. Given their high prevalence, considerable impact on mortality, impact on quality of life and health care use, and associations with each other, screening for and addressing patient and carer anxiety and depression in advanced COPD is recommended. Keywords: COPD, anxiety, depression, informal carers, patient–carer dyad